2020
DOI: 10.1021/acs.est.9b07815
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Hurricanes Reveal Risks and Opportunities for Social-Ecological Resilience to Flooding and Water Quality Problems

Abstract: Hurricanes that damage lives and property can also impact pollutant sources and trigger poor water quality. Yet, these water quality impacts that affect both human and natural communities are difficult to quantify. We developed an operational remote sensing-based hurricane flood extent mapping method, examined potential water quality implications of two "500-year" hurricanes in 2016 and 2018, and identified options to increase social-ecological resilience in North Carolina. Flooding detected with synthetic ape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Second, we didn't consider the spatial extent of surge flooding, only the tide gauge locations. Schaffer-Smith et al (2020) found the total flood extent was similar between the two storms in North Carolina, with Florence causing more extensive flooding in the southeastern part of the state. Third, this is a purely statistical study and does not offer reasons for the difference in spatial compounding between Matthew and Florence.…”
Section: Discussionmentioning
confidence: 86%
“…Second, we didn't consider the spatial extent of surge flooding, only the tide gauge locations. Schaffer-Smith et al (2020) found the total flood extent was similar between the two storms in North Carolina, with Florence causing more extensive flooding in the southeastern part of the state. Third, this is a purely statistical study and does not offer reasons for the difference in spatial compounding between Matthew and Florence.…”
Section: Discussionmentioning
confidence: 86%
“…Because they are collected posterior to the event, HWMs do not have date information specific to the time of peak flooding. However, they can still be used as evidence of inundated/non‐inundated conditions near the site (Schaffer‐Smith et al., 2020), thus aiding visual interpretation of high‐resolution aerial/satellite imagery from NOAA and Google Earth (with specific collection date information) to identify flood hotspots and manually digitized ground reference polygons. Finally, by overlaying the randomly generated points with these flood‐related datasets (such as HWM and high‐resolution aerial/satellite imagery), we manually digitized polygons near each point and visually interpreted and labeled them in 9 different classes (Figure S1a and Table S3 in Supporting Information ), including open surface water, open herbaceous vegetation on flood waters, sparse trees in flood waters, inundation beneath forest, wet grassland (or unharvested cropland), dry grassland (or fallow cropland dominated by bare soil), grass‐dominated mosaic landscape, tree‐dominated mosaic landscape, and upland forest.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, domain experts deemed critical the prioritization of catchments by extent of intact, mitigable land that is also under pressure for near‐ and long‐term (i.e., 10–50 years) development. Likewise, anticipated stressors associated with climate change (e.g., frequent flooding, increasing temperatures) motivated participants to prioritize catchments by extent of mitigable land that possesses physical features associated with high site resilience and decrease the risk of impairments across larger geographical domains (Anderson et al, 2014; Schaffer‐Smith et al, 2020). In this context, we define site resilience as intact natural areas that sustain a diversity of species and ecosystems, support essential relationships among ecological systems, and allow for adaptive changes (Anderson et al, 2014).…”
Section: Framework Implementationmentioning
confidence: 99%